Citizen's Guide to the Independent Corrupt Practices And Other Related Offences Commission (Eddy-Asae Ng. Press, 2012)
the socio-Economic Rights and accountability Project (SERAP) ia a non- governmental, non-profit organization established in 2004, under the companies and allied matters decree 1 of 1990 of the republic of Nigeria. SERAP aims to promote transparency and accountability in the public and private sectors through human rights.
Keywords: Non-Fiction